Performans Produksi Ayam Pedaging pada Lingkungan Pemeliharaan dengan Ketinggian yang Berbeda di Sulawesi Selatan (BROILER PRODUCTIONS PERFORMANCE ON THE DIFFERENT BREEDING ALTITUDE IN SOUTH SULAWESI) - Qurniawan, Anas; Arief, Irma Isnafia; Afnan, Rudi (Jurnal Veteriner; Vol 17 No 4 (2016), 2017)
The aim of this study was to identify the environmental factors of chickens based on the different altitudebreeding against the microclimatic and performance production in Takalar district, South Sulawesi. Atotal of 180 Lohmann strain chickens consisted of 90 male chickens and 90 female chickens. A randomizedblock design with two factorial patterns was used in this study. The first factor was based on altitude (low<300 mabove sea level, medium 300-600 m, and high >700 m ), the second factorwas based on gender(male and female). Data were analyzed using analysis of variance (ANOVA) and then the significant effectwas followed with Tukey test. The results showed that the altitudehad a significant effect against thephysiological status (rectal temperature), production performance (feed intake), water intake, final bodyweight, and FCR. The male and female chickens had a significant effect against feed intake, water intake,breeding final body weight, and carcass weight. There was interaction between altitude and sex on weightgain performances. The altitudes may influence the effects of physiological status and productionperformance. The production performance of male seems to behigher than the female.
Keywords: chicken, altitude, microclimatic, production performance